Efektivitas Arab Pegon Dalam Pemahaman Kitab Kuning Di Pesantren Darun Najah Malang - Afifah, Izatul; Sirojudin, Didin (Universitas KH. A. Wahab Hasbullah, 2022)
The kitab kuning is a traditional book that contains Islamic religious lessons that are applied in islamic boarding schools, usually also called bare books, so called because they have no harakat at all. Therefore, to be able to understand the content of the text of the kitab kuning, a certain method is needed, including the Arabic pegon method. The purpose of this study is to describe the effectiveness of the Arabic pegon method in understanding the text of the kitab kuning, the achievements achieved and the advantages and disadvantages of the method. This research uses a qualitative method where the data obtained comes from research documents, interviews, observation results and documentation. Data analysis techniques take three steps which include data reduction, data presentation and drawing conclusions. The results showed that: 1) The implementation of the Arabic pegon method in the Tsanawiyah class was divided into three stages, namely the introduction stage, the preparation stage and the learning stage. 2) The achievements that this method applies include academic and non-academic achievements. 3) The advantages of this method include that students are easier to understand the content of the kitab kuning text because it uses the local language, while the drawbacks if there is no deep understanding of Arabic grammar will spend a long time to understand the kitab kuning